Prevalence and Determinants of Peripheral Neuropathy among Type 2 Adult Diabetes Patients Attending Jimma University Medical Center, Southwest Ethiopia, 2019, an Institutional-Based Cross-Sectional Study - Daba Abdissa; Nigusse Hamba; Kumsa Kene; Deriba Abera Bedane; Guluma Etana; Dassalegn Muleta; Asfaw Gerbi (Journal of Diabetes Research, 2020)
Background. Diabetes chronic complications are major causes of morbidity and mortality, among which diabetic peripheral neuropathy (DPN) stands out. One of the tools to screen DPN is the Michigan neuropathy screening instrument. However, there is no data compiled using this tool to assess the prevalence and its determinants in Jimma. So, the aim of this study was to assess the prevalence of DPN and its determinants among patients with diabetes mellitus at Jimma University Medical Center. Methods. A hospital-based cross-sectional study was conducted at Jimma University Medical Center on 366 type 2diabetic patients. Data were collected using pretested structured questionnaire and entered into EpiData 3.1 and exported to SPSS version 20 for analysis. Both bivariate and multivariate binary logistic regressions were employed to identify factors associated with DPN. A variable having a p value of < 0.25 in the bivariate model was subjected to multivariate analysis to avoid confounding variable’s effect. Adjusted odds ratios were calculated at 95% confidence interval and considered significant with a p value of ≤ 0.05. Results. The mean age of participants was 50.1±14.28 years. The study finding showed that the prevalence of DPN was 53.6% among study participants. According to the multivariate logistic regression age above 40 years (AOR=4.57; 95% CI: 1.50, 13.9), above 50 years (AOR=6.5; 95% CI: 2.24, 18.79), duration of diabetes above 5 years (AOR=3.06; 95% CI: 1.63, 5.77), duration above 10 years (AOR=7.1; 95% CI: 2.99, 17.28), physical inactivity (AOR=2.02; 95% CI: 1.14, 3.55), and smoking (current smoker AOR=7.96, 95% CI: 3.22, 19.64; former smoker (AOR=2.65; 95% CI: 1.22, 5.77) were independent predictors of DPN among study participants. Conclusion. Almost half of the study participants had DPN. Age above 40 years, diabetes duration of above 5 years, physical inactivity, and smoking were significantly associated with DPN. Early detection and appropriate interventions are important among patients with age above 40 years, physically inactive, smokers, and diabetes duration of above 5 years.